2019
DOI: 10.12998/wjcc.v7.i20.3175
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and drug resistance of pathogenic bacteria in emergency patients

Abstract: BACKGROUNDAntibiotic resistance has become a global threat for human health, calling for rational use of antibiotics.AIMTo analyze the distribution and drug resistance of the bacteria, providing the prerequisite for use of antibiotics in emergency patients.METHODSA total of 2048 emergency patients from 2013 to 2017 were enrolled. Their clinical examination specimens were collected, followed by isolation of bacteria. The bacterial identification and drug susceptibility testing were carried out.RESULTSA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Therefore, widespread screen of antibiotics is required for identification of the most effective drug in the synergistic use with the crucial biomarker. More importantly, both SCF-resistant and amikacin-resistant P. aeruginosa is a big challenge to uncontrolled infection in clinic ( Huai et al, 2019 ). Amikacin is one of antibiotics for the treatment of P. aeruginosa with difficult-to-treat resistance infections ( Tamma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, widespread screen of antibiotics is required for identification of the most effective drug in the synergistic use with the crucial biomarker. More importantly, both SCF-resistant and amikacin-resistant P. aeruginosa is a big challenge to uncontrolled infection in clinic ( Huai et al, 2019 ). Amikacin is one of antibiotics for the treatment of P. aeruginosa with difficult-to-treat resistance infections ( Tamma et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of P. aeruginosa isolates resistant to agents recommended for the treatment of hospital-acquired pneumonia ranged 22.2% for amikacin to 50.0% for cefoperazone ( Ding et al, 2016 ). Another investigation in emergency patients from 2013 to 2017 shows higher resistance rates of P. aeruginosa to cefoperazone/sulbactam (SCF) with the resistance increasing year over year, while the resistance rate to amikacin was below 10% ( Huai et al, 2019 ). These investigations suggest that SCF-resistant P. aeruginosa is a great challenge to be controlled and amikacin can be a suitable drug for combatting multidrug-resistant P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 19 of them had multiple Klebsiella pneumoniae infections, while 13 patients had a history of reinfections with various pathogens. Moreover, attention should be paid to the antibiotic resistance of Klebsiella pneumoniae and the antibiotic should be adjusted in time[ 26 ]. We did not analyze the etiology distribution or costs among all the patients due to a lack of research, which is a deficiency of this review.…”
Section: Discussionmentioning
confidence: 99%
“…to β-lactam antibiotics including carbapenem is rife. Huai et al [19] reported Klebsiella pneumoniae isolates that had high rate of resistance to impenem in China. Similarly, Yazdansetad et al [20] a 50% rate of extended spectrum β-lactamase (ESBL) producing K. pneumoniae in Iran.…”
Section: Discussionmentioning
confidence: 99%